PKC-Theta is a Novel SC35 Splicing Factor Regulator in Response to T Cell Activation - McCuaig, Robert Duncan; Dunn, Jennifer; Li, Jasmine; Masch, Antonia; Knaute, Tobias; Schutkowski, Mike; Zerweck, Johannes; Rao, Sudha (Frontiers in Immunology, 2015)
Alternative splicing of nuclear pre-mRNA is essential for generating protein diversity and regulating gene expression. Whilst many immunologically relevant genes undergo alternative splicing, the role of regulated splicing in T cell immune responses is largely unexplored, and the signaling pathways and splicing factors that regulate alternative splicing in T cells are poorly defined. Here we show using a combination of Jurkat T cells, human primary T cells, and ex vivo naïve and effector virus-specific T cells isolated after influenza A virus infection that SC35 phosphorylation is induced in response to stimulatory signals. We show that SC35 co-localizes with RNA polymerase II in activated T cells and spatially overlaps with H3K27ac and H3K4me3, which mark transcriptionally active genes. Interestingly, SC35 remains coupled to the active histone marks in the absence of continuing stimulatory signals. We show for the first time that nuclear PKC-θ co-exists with SC35 in the context of the chromatin template and is a key regulator of SC35 in T cells, directly phosphorylating SC35 peptide residues at RRM and RS domains. Collectively, our findings suggest that nuclear PKC-θ is a novel regulator of the key splicing factor SC35 in T cells.